Dinamika Politik Hukum Ketatanegaraan Indonesia dalam Rangkap Jabatan Politis (Menteri) - Ardiansya, Ariyanto; Sanjaya, Arya (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Currently, dual office holding has become a prevalent political phenomenon, particularly concerning ministers holding positions within political parties. This situation can lead to various problems, such as conflicts of interest and abuse of power. This journal discusses the legal position of dual office holding by ministers in Indonesia’s constitutional system. The purpose of this research is to analyze the application of regulations regarding dual office holding by ministers within Indonesia’s constitutional framework.The type of research used is normative legal research or library research, which involves studying legal materials and/or secondary data. Secondary data is data obtained from other sources, not directly gathered by researchers from their research subjects. These materials are systematically organized, analyzed, and conclusions are drawn regarding the researched issues. The legal framework referred to includes Article 23 of Law Number 39 of 2008 concerning State Ministry Regulations.Based on this research, it is concluded that the implementation of regulations reveals several factors that drive or contribute to dual office holding by ministers, as well as flaws and weaknesses in the legal regulations related to this issue